Water for food security: The contribution of CGIAR in addressing global agricultural water challenges - Xie, Hua; Masso, Cargele (International Food Policy Research Institute, 2025)
Water is a fundamental input for food production and is used extensively across all agricultural activities, including crop cultivation, livestock production, aquaculture, and food processing. Substantial investments have been made to expand water supply capacity for agriculture, which has made a significant contribution to agricultural production growth (FAO, 2021). At the same time, the intensive use of water in agriculture and related processes creates significant pressures on water resources and aquatic ecosystems. Water scarcity and pollution are among the major water-related challenges associated with global food production, which are directly relevant to SDG 6.